Signifikansi Kepemimpinan Tranformational - didin sirojudin (Universitas KH. A. Wahab Hasbullah, 2019)
Speaking of human resource management, leadership is an important factor to be used as a reference in institutional development. Transformative leadership can be an alternative method for leading Islamic education institutions. Therefore, this is where the dimensional function of the concept role is expected to have a major influence on leadership in Islamic Education Institutions. The method and type of data collection in this study is library research by collecting books, journals and the results of previous research that supports research themes, including literature on leadership that includes transformational leadership dimensions. The results of this study indicate that success in leadership is the most important and urgent element in the effort to create quality education from basic education institutions to higher education institutions the more the leadership process runs optimally the easier the shared goals can be achieved. .